The effects of cooling slope on the semi-solid microstructures of Al4.8Si2.8Cu0.5Mg aluminium alloy / Mohd Anif Mohd Arif ... [et al.] - Mohd Arif, Mohd Anif; Omar, Mohd Zaidi; Sajuri, Zainuddin; Mohamed, Intan Fadhlina; Samat, Saziana (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Thixoforming process is a metal forming process in the semi-solid condition to produce near net shaped products. The key requirement of the thixoforming process is the production of feedstock materials that consists of solid spheroids in the liquid matrix, rather than dendrites. The solid spheroidal structure could not be generated if the gravity cast alloy that consists of the dendritic structure is directly subjected to partial remelting. Cooling slope casting process is one of the simplest and cheapest methods that can be utilised to produce the nondendritic structure. In the present study, the effects of cooling slope casting process on the microstructure of Al4.8Si2.8Cu0.5Mg aluminium alloy were investigated. The alloy was melted at a superheated temperature of 700 °C before cooled down to the selected pouring temperature (650 °C) and subsequently poured onto a stainless steel plate with the cooling length of 400 mm. The plate was tilted at 60° from horizontal and was cooled with water circulation underneath to promote the nucleation of fine α-Al particles. Finally, the poured molten metal was collected in a 150 °C preheated cylindrical stainless steel mould. The alloy billet that consists non-dendritic αgrains with a shape factor of 0.74±0.13 and an average primary particle size of 31.94±6.76 µm was successfully produced from gravity cast alloy with a dendritic microstructure by cooling slope casting process. After partial remelting at 575 °C, the non-dendritic structure has changed into fine solid spheroidal α-Al grains with a shape factor of 0.84±0.06 and an average primary particle size, approximately 35.92±9.13 µm. These solid spheroidal structures surrounded by a liquid matrix may be offer thixotropic behaviour and suitable for thixoforming applications.